Efficient RGB-D data processing for feature-based self-localization of mobile robots - Kraft, Marek; Nowicki, Michał; Penne, Rudi; Schmidt, Adam; Skrzypczyński, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The problem of position and orientation estimation for an active vision sensor that moves with respect to the full six degrees of freedom is considered. The proposed approach is based on point features extracted from RGB-D data. This work focuses on efficient point feature extraction algorithms and on methods for the management of a set of features in a single RGB-D data frame.
Keywords: visual odometry; simultaneous localization and mapping; RGB-D; tracking; point features